Prevalence, Correlates, and Trends of Intimate Partner Violence Against Women in Cambodia: Findings From 2014 and 2021-22 Cross-Sectional Demographic and Health Surveys - Masood Ali Shaikh MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2024)
Intimate partner violence (IPV) is globally endemic and a gross violation of human rights, in addition to abuse of intimacy by some men against their female intimate partners. Based on literature review, attitudinal, socio-demographic, and experiential attributes of 15 to 49 year old ever partnered women in the heterosexual relationships were identified. This study used the anonymized 2020-21Cambodia Demographic and Health Survey (CDHS) data to compute the IPV prevalence and its correlates, in addition to computing the changes in IPV prevalence at the urban, rural, and at the national levels using data from the 2014 CDHS. Identified attitudinal, socio-demographic, and experiential attributes were used in the bivariate and multivariable analysis. Simple and multiple logistic regression models were used for computing the bivariate and multivariate associations with IPV; additionally, trend analysis was done to compute changes in IPV prevalence between the 2 surveys. Lifetime prevalence of IPV was 20.70%, while the most common subtype was emotional IPV at 18.70%. Ten out of 12 correlates studied were found to be statistically significantly associated with IPV in the bivariate analysis. These were added in the multivariable model and 7 were found to be statistically significantly associated with IPV. Which included educational attainment of women and their intimate partners, number of living children, women’s IPV acceptance, male partner’s alcohol use, knowledge of physical beating of mother by one’s father, and controlling behavior exercised by partner. During the intervening period between the 2 CDHSs, IPV and its subtypes were decreased in both urban and rural areas, as well as nationally. IPV decrease between the 2 DHSs and lower IPV rates in 2021-22 augur well for the health and human rights of Cambodian women. However, the ultimate target of eliminating IPV against women, will require measures that ensure economic and gender empowerment, and gender equality.